Analysis of the RS10750097 and RS3741298 polymorphisms of the APOA5 genes in relation to dyslipidemia (Revista Contexto & Saúde, 2025)
Dyslipidemia is characterized by a disorder in lipid metabolism and arises from external causes or predisposing genetic disorders. This observational, cross-sectional study aimed to analyze the correlation between the genetic polymorphisms RS10750097 and RS3741298 associated with the lipoprotein ApoA5-ZNF259 and the development of dyslipidemia. A sample of 200 Military Police officers from the state of Goiás was used, and genotyping of the polymorphisms was performed. Regarding the participating individuals, 93% were male and 7% were female. The polymorphisms observed in the groups with and without dyslipidemia showed a significant difference between the two groups for all variables analyzed (p
Keywords: Dyslipidemia; APOA5; ZNF; polymorphism; military; genes